E-154 A novel phantom model for chronic subdural hematoma evacuation. (23rd July 2022) - Morgan, I; Baker, T; Rapoport, B; Bederson, J; Rodriguez, B; Williams, T; Borello, J; Durbin, J
Abstract : Introduction: Training neurosurgeons is a challenging task due to the complex, time-consuming, and case-specific procedures that they must master. Cadaver models often lack the physiological characteristics necessary to replicate a procedure and animal models are not always accurate or available. The development of case-specific phantom models is necessary to increase the number of procedures each trainee is exposed to and, as a result, improve the quality of education. These models are especially relevant in minimally invasive procedures, such as burr-hole chronic subdural hematoma (CSDH) evacuation, which doesn't have a proper cadaver or animal model. Materials and Methods: A novel phantom model was created, incorporating powder-based 3D printing technology with hydrogel tissue modeling to accurately recreate a 60mL chronic subdural hematoma case. The skull model was constructed utilizing 3D-powder-based printing and the 3D silicone brain model was built with a 10% polyvinyl alcohol mixture. Similarly, the dura was cast with the same polyvinyl alcohol concentration to be 1mm(H) x 10 cm(W) x 8 cm(L). The hematoma was created by encasing, in a thin plastic sack, a 4:2 water and gelatin mixture totaling 60mL. Simulated CSDH evacuation surgery consisted of visualizing the hematoma with an endoscope and removing it with an active evacuator. Following the evacuation, participating biomedical engineers were asked to rate the model's accuracy on a five-point scale, from 'highly accurate' to 'poorly accurate, ' while focusing on four major elements: (1) Skull composition, (2) Dura composition, (3) Hematoma composition, and (4) Overall Model. Results: The model was able to recreate a CSDH, enabling the successful evacuation of subdural hemorrhage with neuroendoscopy. The evacuation from initiation of aspiration to completion was conducted in 228 seconds, resulting in the evacuation of 84.58% of the hematoma. Skull composition performed best, with all raters rating it as 'highly accurate.' Hematoma composition received the worst score, with the major complaint being the lack of coagulation simulated. Conclusions: The phantom model was shown to successfully reproduce a CSDH. Hematoma consistency is currently poor; however, incorporation of an improved coagulant simulant is currently underway. An additional study collecting feedback from residents and practicing neurosurgeons is being designed and will be initiated within 2022. Phantom models are a useful tool for the training of new surgeons and both, refinement, and development of novel techniques. The model shown here demonstrated a subdural hematoma model that is highly customizable, inexpensive, and requires no special disposal, unlike animal and cadaver models. Disclosures: I. Morgan: None. T. Baker: None. B. Rapoport: None. J. Bederson: None. B. Rodriguez: None. T. Williams: None. J. Borello: None. J. Durbin: None.